On some regularities in dynamic response of cyclic periodic structures - Krzyzynski, Tomasz; Popp, Karl; Sextro, Walter (Chaos, Solitons & Fractals)
The paper deals with cyclic periodic structures modelling bladed disk assemblies of blades with friction elements for vibration damping. These elements placed between adjacent blades reduce the vibration amplitudes by means of dry friction resulting from centrifugal forces acting on the elements and relative displacements of the blades. However, the application of these friction elements results in an additional dynamical coupling which together with mistuning of some system parameters (e.g., blade eigenfrequency or contact parameters) may cause localization of vibration. In the present paper a linear approximation of such a system is investigated. The structure composed of cyclic periodic cells modelled each as a clamped-free beam interacting with each other by means of viscoelastic elements of complex stiffness is applied for dynamic system analysis. In case of free vibrations as well as in case of steady-state dynamic response to a harmonic pressure field, a perfect periodic structure and the structures with periodically mistuned parameters (blade eigenfrequencies and contact parameters) are studied. Some regularities in the dynamic response of the systems with mistuning have been noticed. Despite the fact that only a linear approximation has been used, the results and conclusions can be applied for models which describe the blade interaction in a nonlinear way.

Optimization of Interblade Friction Damper - Panning, Lars; Sextro, Walter; Popp, Karl (International Gas Turbine & Aeroengine Congress & Exhibition, ASME)
the vibration amplitudes of bladed disk assemblies can be reduced significantly by means of friction damping devices such as shrouds, damping wires and interblade Friction dampers. in practice, interblade Friction dampers are applied in rotating arrangements with various geometries showing curved or flat surfaces like so-called wedge-shaped dampers. this paper is focusing on a computation method to predict the dynamical behaviour of turbine blades with Friction dampers including both, curved and wedge-shaped dampers with hertzian and non-herutian contact conditions, respectively. the presented computation method uses a 3d contact model to calculate the contact forces, including normal and tangential stiffnesses, roughness and microslip effects. the relative displacements in the contact area can be expressed by means of 6 dof of the blade platforms and 6 rigid body dof of the damper including translational and rotational displacements. the relative displacement of the Friction damper with respect to the adjacent blades can be derived from the contact kinematics of the blade-damper-blade system and the equations of motion of the Friction damper. thus, the model can be applied to investigate spatial motions of the bladed disk assembly including bending and torsional vibrations. a comparison of different Friction damper designs with respect to an optimal damper geometry and damper mass is presented. the advantages and disadvantages of each design will be discussed. experimental results are shown to validate the developed computation method.

The Calculation of the Forced Response of Shrouded Blades with Friction Contacts and Its Experimental Verification - Sextro, Walter (International Gas Turbine & Aeroengine Congress & Exhibition, ASME)

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Experimental verification of a non-Hertzian contact model - Sextro, Walter (International conference on computational methods in contact mechanics)

Forced Vibration of Elastic Structures with Friction Contacts - Sextro, Walter (ASME Design Engineering Technical Conferences)

Ein ebenes Reibkontaktmodell zur Berechnung von Schaufelschwingungen mit Reibelementen - Sextro, Walter; Popp, Karl (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW))

Modellierung piezoelektrischer Stapel- und Vielschichtaktoren für dynamischen Betrieb - Hemsel, Tobias; Krome, Jürgen; Littmann, Walter; Wallaschek, Jörg (Proceedings 2. Polnisch-Deutscher Workshop "Werkzeuge der Mechatronik")

A piezoelectric linear vibration drive for high driving forces - Hemsel, Tobias; Wallaschek, Jörg (Proceedings of VIBROENGINEERING)

Vibrational Behaviour of Tuned and Detuned Bladed Disks with Friction Dampers - Sextro, Walter; Popp, Karl; Wolter, I (International Congress on Combustion Engines, Proceedings of the 22nd CIMAC)

Three-Dimensional Vibration of Bladed Disk Assemblies with Friction Dampers - Sextro, Walter; Popp, Karl; Wolter, I (The 7th International Symposium on Transport Phenomena and Dynamics of Rotating Machinery, Proceedings of ISROMAC-7)

Schwingungsprüfstand zur vollautomatischen Messung von Ultraschallschwingungen in piezoelektrischen Antrieben - Goldschmidt, Stefan; Hemsel, Tobias; Krome, Jürgen; Storck, Heiner; Wallaschek, Jörg (Tagungsband zum 4. Laser Vibrometer Seminar der Polytec GmbH)

Ultrasonic motors for linear positioning tasks in automobiles - Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 30th International Symposium on Automotive Technology & Automation (ISATA))
Piezoelectric ultrasonic motors are a new kind of actuators that produce high driving-forces related to their volume. Beside rotary drives like the travelling wave motor many linear drives have been developed and are already commercially available today. These motors can provide static holding-forces and driving-forces of up to 30 N at velocities of up to 220 mm/s. These operational characteristics, which are expected to be improved continuously, make these devices attractive as direct-drives for sliding roofs or windows in automobiles. In this contribution a short outline of the present state-of-the-art of linear ultrasonic motors is given. Different operating principles are compared with respect to the potential driving-force and power. Finally the working-principle of a newly developed motor, which uses the piezoelectric d33-effect, is explained in detail. Theoretical and experimental results show that this motor is capable of achieving high driving-force and rated output-power

Piezoelectric ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (EUROMECH, European Mechanics Colloquium "Synthesis of Mechatronic Sytems")

Schwingungsverhalten von verstimmten Beschaufelungen mit Reibelementen - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Schwingungsverhalten von Schaufelkränzen mit Reibelementen bei Frequenzverstimmung - Sextro, Walter (VDI-Reihe)

Improved reliability of bladed disks due to friction dampers - Sextro, Walter; Popp, Karl; Wolter, Ivo (The 1997 International Gas Turbine & Aeroengine Congress & Exposition)

Schwingungsverhalten eines Schaufelkranzes mit Reibelementen bei Frequenzverstimmung - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) - lnformationstagung Turbinen)

Dynamical Behaviour of a Bladed Disk with Friction Dampers - Popp, Karl; Sextro, Walter (The 2nd European Nonlinear Oscillation Conference - Proceedings of EUROMECH)

Static Behaviour of Drill Strings in Curved Boreholes - Sextro, Walter; Schmalhorst, B (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Bifurcations in Dynamic Systems with Dry Friction - Stelter, Peter; Sextro, Walter (Bifurcation and Chaos: Analysis, Algorithms, Applications)
Dry friction is a main factor of self-sustained oscillations in dynamic systems. The mathematical modelling of dry friction forces result in strong nonlinear equations of motion. The bifurcation behaviour of a deterministic system has been investigated by the bifurcation theory. The stability of stationary solutions has been analyzed by the eigenvalues of the Jacobian. Period doublings and Hopf-bifurcations as well as turning points could be determined with the program package BIFPACK. Phase plane plots of periodic and chaotic motions have been shown for a better understanding of the bifurcation diagrams. Both, unstable branches and stable coexisting solutions have been calculated. Several jumping effects, which are typical for nonlinear systems, have been found.